NILAI OYAGOKORO DALAM ANIMASI CERITA RAKYAT JEPANG SEBAGAI MEDIA EDUKASI PENGUAT IKATAN ORANG TUA DENGAN ANAK - Suryani, Putu Ayu (Prosiding Seminar Nasional Bahasa Ibu, 2025)
Folktale can be used as a medium to educate and build or shape the character of a nation that is passed down from generation to generation. In addition, folktale can also contain messages and values ??of affection between parents and children. The affection of parents to children in Japanese is called ?? oyagokoro. The affection of parents to children in some folktale is not always represented by the parent and child figures who have blood ties. Characters such as Momotarou, Kaguya-hime, and Shiro in Japanese folktale are characters who were raised by a husband and wife who were not their biological parents, but the three characters grew up to be dutiful children. This phenomenon shows that an analysis is needed to find similarities between the three folktales. This study is a qualitative study with three Japanese folktales entitled (1) Momotarou, (2) Kaguyahime, and (3) Hanasaka Jiisan in animation format as data sources. The data collection method in this study is the observation method supported by recording and translation techniques. The data of this study are in the form of narratives and dialogues in the three folktales, then the data are analyzed using the theory of oral literature functions by Bascom and presented using informal methods. The results of the analysis show that the affection of the grandfather and grandmother figures in the three folktales has the same characteristics, namely starting with accepting the existence of the child figure, giving a name, caring for it wholeheartedly, and feeling heavy when separated. This shows that the grandfather and grandmother figures have oyagokoro 'parental affection for children'. The similarity of the oyagokoro elements in the three folktales shows that animated folktales can function as an educational medium to strengthen the bond between parents and children.